Improving the ability of speaking students of SMK Sentra Medika Medan with modeling methods as extenders for covid-19 - Gustianingsih; harahap, Nurhayati; Lubis, Haris Sutan; Marsella, Emma; Guniesti, Veryani (Talenta Publisher, 2020)
This Community Service program aims to improve the speech skills of students of SMK Sentra Medika Medan and train to become extension agents in the health sector, especially in dealing with Covid-19. The method of increasing the ability to speak is carried out by the modeling method, namely by presenting a model in the form of figures who are considered skilled at speeches to be reviewed and imitated by good things from technique, voice or intonation, style or gesture, and others which are good requirements for speech. The results of this training are: (1) Improve the ability of students of SMK Sentra Medika Medan in making public speeches. (2) Increasing the sensitivity of students of SMK Sentra Medika Medan to conditions that threaten health in the surrounding environment. (3) Providing speech training for students of SMK Sentra Medika Medan. (4) Students of SMK Sentra Medika Medan learn to make speeches so that they are trained to become extension agents to overcome health problems, in this case, with COVID-19 material.